2014
DOI: 10.3390/ma7127843
|View full text |Cite
|
Sign up to set email alerts
|

The Fire Resistance Performance of Recycled Aggregate Concrete Columns with Different Concrete Compressive Strengths

Abstract: In order to ascertain the fire resistance performance of recycled aggregate concrete (RAC) components with different concrete compressive strengths, four full-scaled concrete columns were designed and tested under high temperature. Two of the four specimens were constructed by normal concrete with compressive strength ratings of C20 and C30, respectively, while the others were made from recycled coarse aggregate (RCA) concrete of C30 and C40, respectively. Identical constant axial forces were applied to specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…One of the reasons that could justify the hypothesis of the RACs having the best behavior in the event of a fire is that they have lower thermal conductivity, and therefore, a lower penetration rate of the temperature towards the interior of the cross section. This fact could be observed in experimental tests on full-scale reinforced concrete columns carried out by Dong et al [26]. Table 1 summarizes the main experimental campaigns carried out on RAC at high temperatures, breaking down, by columns, the most relevant variables under study.…”
Section: Introductionmentioning
confidence: 78%
“…One of the reasons that could justify the hypothesis of the RACs having the best behavior in the event of a fire is that they have lower thermal conductivity, and therefore, a lower penetration rate of the temperature towards the interior of the cross section. This fact could be observed in experimental tests on full-scale reinforced concrete columns carried out by Dong et al [26]. Table 1 summarizes the main experimental campaigns carried out on RAC at high temperatures, breaking down, by columns, the most relevant variables under study.…”
Section: Introductionmentioning
confidence: 78%
“…To encourage the use of RCA worldwide, it is also critical to assure its behavior under extreme conditions, one of those is structural fire endurance. There is only limited number of studies on the performance of RCA when subjected to elevated temperatures [39][40][41][42][43][44]. These studies except the study by Dong et al [43] were carried out on small scale cylinder specimens, and reported the hardened properties of concrete such as compressive strength, splitting tensile strength, modulus of elasticity.…”
Section: Test Resultsmentioning
confidence: 99%
“…Although more complex FE models [16,[24][25][26] have been established to study the mechanical behavior of RC structures at elevated temperatures, one of the main objectives of this study is to develop a simplified numerical approach able to predict the global response of RC beams exposed to fire and simultaneously releasing the computational burden. A one-dimensional spectral element model will be implemented in this study to analyze the mechanical behaviors of RC beams; it will be briefly presented since it has been detailed in [27,28], to simulate RC beams that are externally bonded with fiber-reinforced polymer strips and interfacial debonding damage.…”
Section: Spectral Element Model For Rc Beamsmentioning
confidence: 99%